Prospective pragmatic quasi-experimental study to assess the impact and effectiveness of an innovative large-scale public health intervention to foster healthy ageing in place: the SoBeezy program protocol. Issue 4 (29th April 2021) - Pérès, Karine; Zamudio-Rodriguez, Alfonso; Dartigues, Jean-Francois; Amieva, Hélène; Lafitte, Stephane
Abstract : Introduction: With the accelerating pace of ageing, healthy ageing has become a major challenge for all societies worldwide. Based on that Healthy Ageing concept proposed by the WHO, the SoBeezy intervention has been designed through an older person-centred and integrated approach. The programme creates the environments that maximise functional ability to enable people to be and do what they value and to stay at home in best possible conditions. Methods and analysis: Five levers are targeted: tackling loneliness, restoring feeling of usefulness, finding solutions to face material daily life difficulties, promoting social participation and combating digital divide. Concretely, the SoBeezy programme relies on: (1) a digital intelligent platform available on smartphone, tablet and computer, but also on a voice assistant specifically developed for people with digital divide; (2) a large solidarity network which potentially relies on everyone's engagement through a participatory intergenerational approach, where the older persons themselves are not only service receivers but also potential contributors; (3) an engagement of local partners and stakeholders (citizens, associations, artisans and professionals). Organised as a hub, the system connects all the resources of a territory and provides to the older person the best solution to meet his demand. Through a mixed, qualitative and quantitative (before/after analyses and compared to controls) approach, the research programme will assess the impact and effectiveness on healthy ageing, the technical usage, the mechanisms of the intervention and conditions of transferability and scalability. Ethics and dissemination: Inserm Ethics Committee and the Comité Éthique et Scientifique pour les Recherches, les Études et les Évaluations dans le domaine de la Santé approved this research and collected data will be deposited with a suitable data archive.